Metacognitive study strategies in a college course and their relation to exam performance. - Zepeda, Cristina D.; Nokes-Malach, Timothy J. (Memory & Cognition, 2021)
Several strands of prior work have evaluated students' study strategies and learning activities. In this work, we focus on integrating two of those strands. One has focused on student self-reports of their study practices from a cognitive psychology perspective. The other has focused on classifying student learning activities from a learning sciences perspective using the Interactive, Constructive, Active, and Passive (ICAP) framework (Chi & Wylie, 2014). The current study aims to integrate these two strands of research by testing the implications of the ICAP framework with students' self-reports in a classroom context. Another goal was to address the measurement limitations of the metacognitive study strategy literature by using assessment-specific self-reports with both closed and open-ended questions. Across three noncumulative exams, 342 undergraduates self-reported their study practices before each exam. We then categorized their strategies as either active or constructive in alignment with the ICAP framework. Next, we examined whether these strategies were related to each other and then tested the hypothesis that constructive strategies would be positively associated with better exam performance than active strategies. Students reported using a variety of study practices in which a few active strategies were related to constructive strategies, but constructive strategies were more likely to be related to each other. Lastly, supporting the ICAP framework, many of the constructive strategies were positively related to exam performance, whereas the active strategies were not. This work provides insight into the measurement of students' study strategies and their relations to each other and learning outcomes.